If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8n = 7(2n + 7) Reorder the terms: 8n = 7(7 + 2n) 8n = (7 * 7 + 2n * 7) 8n = (49 + 14n) Solving 8n = 49 + 14n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14n' to each side of the equation. 8n + -14n = 49 + 14n + -14n Combine like terms: 8n + -14n = -6n -6n = 49 + 14n + -14n Combine like terms: 14n + -14n = 0 -6n = 49 + 0 -6n = 49 Divide each side by '-6'. n = -8.166666667 Simplifying n = -8.166666667
| 1-6(-2x-6)=109 | | R^2+12r-66=-6 | | -4/7=?/28 | | ln(7x)=81 | | (X+2)-4-6x=3x+10 | | 91=-7(7-4k) | | 14=z-y | | -5n-7=23 | | Cosx=2sinx | | -6-6x=1x+4 | | 14a^2+7a-196=0 | | 355=-5n-5(8n-8) | | 2cos^2x+5sinx-5=0 | | 1/9=?/45 | | (X+2)-2(4-3x)=2(x+4)-4 | | (-7)-x=-5 | | 9n^2+94n-168=0 | | 7x-8=55-2x | | (-3)-x=2 | | p-12=218 | | .5x^2=8 | | -6a=36a | | y=2x-5x+7 | | 2.9r=-5.7t-5 | | x-(-14)=-11 | | 5y-9=7+y | | 60-what+10=20 | | 5=1-4(-5) | | 3m-7=m-13 | | 3x+9x+5=17 | | 4-5p=8 | | 2(X+8)+5x-9=3(X+2)+4(2x+9)-5(3x+8)+25-12x |